Perbedaan Tingkat Kebugaran Jasmani Siswa SMP Berdasarkan Letak Geografis - Lungit Wicaksono; Satria Kusuma; Ridho afiegi Alfadhil (Institut Teknologi Bandung, 2021)
Differences in a person's geographical location can determine the level of physical activity, so that it can be a picture to balance the physical activity of the two places. The purpose of this study was to compare the fitness and physical strength of junior high school students living in low and highlands. This research uses an observational study method, where all subjects will be taken data at one time. 30 male junior high school students with an average age of 13.48 0.79 years, body weight 47.95 ± 4.48 kg and height 157.94 ± 4.99 cm participated in this study. where the total subject will be divided into 2 groups consisting of 15 junior high school students from the lowlands and 15 junior high school students from the highlands. The results showed that the fitness status and physical strength of junior high school students living in highlands had good scores when compared to students living in lowlands. Thus it can be concluded that a person's geographical location affects a person's fitness. These findings can be used as consideration for teachers at schools in order to balance the fitness status of students who live at low altitudes so that they can have good physique like students who live at high altitudes.